TRANSFORMASI SENI JEMBLUNG: STUDI KASUS JEMBLUNG ON THE WAY - Alvian Halif Sinatrya; Denis Setiaji (TAMUMATRA, 2025)
"Jemblung On The Way" (JeOTW) operates in the field of wayang, specifically Contemporary Jemblung. The concept presented, including its musical accompaniment, differs from traditional Jemblung, as its performances address current social issues through puppet characters that resonate with young people and are accompanied by contemporary music. This research employs a qualitative method with a phenomenological approach, which aims to gather data from the practitioners objectively and also attempts to present the pure process undertaken by the practitioners to answer the research questions. The theory used in this study is Umar Kayam’s Cultural Transformation Theory as the Grand Theory to address this research. What JeOTW is doing represents an effort to effectively discover the ethical and aesthetic essence of the Jemblung community in this era. The creation of this new form is evidence of a cultural strategy that allows Jemblung art to adapt to the times.